The Arabic Language Contribution to The Istinbāṭ in Islamic Law of Acehnese Scholars - Muslim, Buhori; Wildan, T.; M. Saman, Syarifuddin; Sufyan, Nurchalis; Mawar, Sitti (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This article discusses the contribution of the Arabic language to the istinbāṭ in Islamic law of Acehnese scholars. The purpose of this journal is to identify the contribution of the Arabic language to the practice of Islamic law. This research is qualitative research using the descriptive analysis method by describing and identifying the influence and contribution of the Arabic language on Islamic legal istinbāṭ among Acehnese scholars. The results of the findings of this study indicate that the primary sources for performing Islamic legal istinbāṭ are the Qur’an, hadīṡ, ijmā‘, and qiyās, all of which are written in the Arabic language. Importantly, the Arabic language greatly contributes to legal istinbāṭ among Acehnese scholars, the more a cleric understands the Arabic language, the easier it is to practice law, and it is important for scholars to master the Arabic language and its literature, such as balaghah, ma‘āni, badi‘, bayān, majāz, nahwu, and sharf because to understand the Arabic language is the inseparable and correlated understanding between sciences which is an integral unit, so that if a scholar performs Islamic law istinbāṭ but does not understand the Arabic language sciences, the legal fatwa he issued will be doubted.